Seasonality of algal communities in small streams and ditches in temperate regions using delayed fluorescence. Issue 3 (2nd July 2016) - Breuer, Friederike; Janz, Philipp; Farrelly, Eamonn; Ebke, Peter
ABSTRACT: Because of their high ecological relevance, algae are often used in environmental monitoring of freshwater ecosystems. They are used to assess the state of the environment, and can be used to estimate the diversity and productivity of the ecosystem. Chlorophyll a is the most commonly used indicator where no taxonomic information is obtained. In this two-year study, algae were monitored in small lotic waterbodies using a high precision method of evaluating algal pigments: delayed fluorescence (DF). The method allows quantifying algae and differentiating algal groups using pigments unique to each algal group. DF correlated strongly with biovolume (derived from cell count) data ( r 2 = 0.94) and could therefore be recommended as a biomonitoring tool. In addition, seasonal dynamics in both the attached and suspended algal communities were studied. Both algal fractions displayed seasonal variations with either a single peak in biomass in summer (type 1), or with two peaks in biomass in spring and fall (type 2). Green algae dominated type 1 patterned communities whereas diatoms dominated type 2 patterned communities. Spatial synchronicity between sampling sites and waterbodies was observed within the studied watershed. Sampling time rather than spatial site selection was found to be a key factor in the study of algal communities in lotic bodies of water.